2003
DOI: 10.1890/0012-9658(2003)084[1539:tropda]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant Diversity and Composition for Nitrate Leaching in Grasslands

Abstract: The relationship between plant diversity and nitrate leaching into groundwater was investigated in a mid‐European semi‐natural grassland ecosystem. An experimental approach was used to directly manipulate plant diversity in the field, while holding other environmental factors constant. Species loss was simulated by establishing grassland communities of 16, 8, 4, 2, 1, and 0 plant species, composed of 3, 2, or 1 functional groups (grasses, legumes, and non‐legume herbs). Every diversity treatment was replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
235
4
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(269 citation statements)
references
References 45 publications
16
235
4
9
Order By: Relevance
“…However, the loss of soil biodiversity may have indirectly resulted in changes in some ecosystem functions. Specifically, the effect of the different soil communities on plant productivity and diversity may have consequently indirectly influenced carbon sequestration and nutrient losses through leaching (43,44). Additionally we also assessed the effects of litter decomposition and N turnover on nutrient losses from the system.…”
Section: Methodsmentioning
confidence: 99%
“…However, the loss of soil biodiversity may have indirectly resulted in changes in some ecosystem functions. Specifically, the effect of the different soil communities on plant productivity and diversity may have consequently indirectly influenced carbon sequestration and nutrient losses through leaching (43,44). Additionally we also assessed the effects of litter decomposition and N turnover on nutrient losses from the system.…”
Section: Methodsmentioning
confidence: 99%
“…Plant available soil N is generally concentrated in the upper soil layers, but may leach to deeper layers, especially in grasslands that include legumes (Scherer-Lorenzen et al 2003) and under conditions with surplus precipitation (Thorup-Kristensen 2006). To improve soil N use efficiency in temporary grasslands, we propose the addition of deeprooting plant species to a mixture of perennial ryegrass and white clover, which are the most widespread forage plant species in temporary grasslands in a temperate climate (Moore 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bardgett et al (1998) and Wardle et al (1999) have reported that the abundance, activity, and composition of soil decomposer communities may vary markedly with differ-ent plant species, or specific functional plant groups such as legumes. Legumes can positively affect the microbial biomass due to high litter quality, that is, litter with a lower C/N ratio (Spehn et al, 2000;Scherer-Lorenzen et al, 2003;Bartelt-Ryser et al, 2005). Experiments of mixed versus monocultured plant species have demonstrated that plant mixtures can produce greater plant biomass (DeBell et al, 1997;Forrester et al, 2004), and improve nutrient cycling and soil fertility (Binkley et al, 1992(Binkley et al, , 2000Bauhus et al, 2000;Montagnini et al, 2000).…”
Section: Introductionmentioning
confidence: 99%